2005
DOI: 10.1038/nature04175
|View full text |Cite
|
Sign up to set email alerts
|

BMP inhibition-driven regulation of six-3 underlies induction of newt lens regeneration

Abstract: Lens regeneration in adult newts is a classic example of faithfully regenerating an entire organ via transdifferentiation1-6. After lentectomy, intriguing regulation allows the pigment epithelial cells (PECs) of the dorsal iris, but not the ventral, to dedifferentiate and then differentiate to form a new lens. This regulation might provide clues to the lack of lens regeneration in higher vertebrates. Six-3 and pax-6 known for their ability to induce ectopic lenses during embryogenesis7,8 and members of the BMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 18 publications
3
102
1
Order By: Relevance
“…Contrary to its early role in embryonic lens specification and induction, Pax-6 appears to play a role during the later stages of regeneration. One line of evidence that supports this notion is that overexpression of Pax-6 in newt ventral iris PECs did not induce transdifferentiation of the ventral iris into lens [32]. Further evidence pointing to a role of Pax-6 in later events of lens regeneration such as proliferation of both the dorsal and ventral iris PECs and regulation of crystallin synthesis has been shown through the use of morpholino technology.…”
Section: Pax-6supporting
confidence: 57%
See 3 more Smart Citations
“…Contrary to its early role in embryonic lens specification and induction, Pax-6 appears to play a role during the later stages of regeneration. One line of evidence that supports this notion is that overexpression of Pax-6 in newt ventral iris PECs did not induce transdifferentiation of the ventral iris into lens [32]. Further evidence pointing to a role of Pax-6 in later events of lens regeneration such as proliferation of both the dorsal and ventral iris PECs and regulation of crystallin synthesis has been shown through the use of morpholino technology.…”
Section: Pax-6supporting
confidence: 57%
“…Perhaps it is the increase in Six-3 expression above the normal threshold levels for both the dorsal and ventral iris that is the key to inducing lens regeneration as opposed to the relative amount of Six-3. Treatment of ventral iris PECs with Six-3/RA causes the ventral iris tissue to adopt an expression profile similar to that seen in the dorsal iris during lens regeneration [32]. In relation to the BMP pathway, we have shown that treatment of newt ventral iris tissue with chordin increases the expression of Six-3 and Pax-6 [32].…”
Section: Six-3mentioning
confidence: 86%
See 2 more Smart Citations
“…They achieve this by the process of transdifferentiation of terminally differentiated cells at the site of the injury. During this process one cell type changes to another, by dedifferentiating [3][4][5]. It is conceivable that such an event may involve global changes in gene expression, implicating a large number of genes [6].…”
Section: Introductionmentioning
confidence: 99%